2008
DOI: 10.1016/j.schres.2008.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing abnormalities in schizotypal personality disorder: An fMRI experiment using tones of deviant pitch and duration

Abstract: Background-One of the cardinal features of schizotypal personality disorder (SPD) is language abnormalities. The focus of this study was to determine whether or not there are also processing abnormalities of pure tones differing in pitch and duration in SPD.Methods-Thirteen neuroleptic-naïve male subjects met full criteria for SPD and were groupmatched on age and parental socioeconomic status to 13 comparison subjects. Verbal learning was measured with the California Verbal Learning Test. Heschl's gyrus volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…For example, reduced left Heschl gyrus was found in male SPD (Dickey et al, 2002), and a volume of the left STG in female SPD was associated with odd speech (Dickey et al, 2003). Furthermore, in a recent fMRI study (Dickey et al, 2008) that used MMN-like paradigm (block design), more activation was found in the STG, bilaterally, to pitch deviants in the SPD relative to normal comparison individuals.…”
Section: Discussionmentioning
confidence: 92%
“…For example, reduced left Heschl gyrus was found in male SPD (Dickey et al, 2002), and a volume of the left STG in female SPD was associated with odd speech (Dickey et al, 2003). Furthermore, in a recent fMRI study (Dickey et al, 2008) that used MMN-like paradigm (block design), more activation was found in the STG, bilaterally, to pitch deviants in the SPD relative to normal comparison individuals.…”
Section: Discussionmentioning
confidence: 92%
“…There are also findings at various regions within the temporal lobe that initially pointed toward an abnormality, although a later study contradicted the initial findings (e.g. Heschl's gyrus (Dickey et al, 2002b(Dickey et al, , 2008). However, a finding of reduced left superior temporal gyrus volume was observed in males with SPD (Dickey et al, 1999) and females with SPD who also had a family history of schizophrenia (Dickey et al, 2003a).…”
Section: Structural Neuroimagingmentioning
confidence: 84%
“…A total of 54 studies described in 49 publications (2 included both MRI/fMRI (Dickey et al, 2008(Dickey et al, , 2010 and 3 included both MRI/PET (Hazlett et al, 1999;Haznedar et al, 2004;Shihabuddin et al, 2001)) met inclusion criteria. The studies include a total non-independent sample of 1181 SPD and 21,055 healthy control subjects.…”
Section: Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SPD-associated gray matter volume reduction has been found in the superior temporal gyrus 20, 28-32 , a region implicated in auditory processing 33 which is impaired in SPD 34 . Gray matter volume reductions have also been reported in other temporal cortex regions, such as Heschl’s gyrus 35 , middle temporal gyrus 20, 36 and inferior temporal gyrus 36 , but less consistently 37 .…”
mentioning
confidence: 99%